Identification of IFN-Induced Transmembrane Protein 1 With Prognostic Value in Pancreatic Cancer Using Network Module-Based Analysis - Wu, Lingyun; Zhu, Xinli; Yan, Danfang; Tang, Mengmeng; Ma, Chiyuan; Yan, Senxiang (Frontiers in Oncology, 2021)
Despite improvements reported in diagnosis and treatments in recent decades, pancreatic cancer still characterized with poor prognosis and low survival rate among solid tumors. Intensive interests have grown in exploring novel predictive biomarkers, aiming to enhance the efficiency in early detection and treatment prognosis. In this study, we identified the differentially expressed genes (DEGs) in pancreatic cancer through analyzed five gene expression profiles, and established the functional modules according to the functional interaction (FI) network between DEGs. Significant upregulation of the selected DEG, IFITM1, was evaluated in several bioinformatics online tools and verified with immunohistochemistry staining from 90 pancreatic cancer patients’ samples. Prognostic data showed that high expression of IFITM1 associated with poor survival and multivariate Cox regression analysis showed that IFITM1 was one of independent prognostic factor for the overall survival. Meanwhile, significant correlations of the expression of IFITM1 and the infiltration of immune cells were found by TIMER. Furthermore, higher level of IFITM1 was assessed in pancreatic cancer cell lines compared to normal human pancreatic duct epithelial cell and silencing IFITM1 in tumor cells remarkedly inhibited the cancer tumorigenicity. Collectively, our findings suggested that IFITM1 might have promising utility for pancreatic cancer.